Patients With Infantile Nephropathic Cystinosis in Germany and Austria: A Retrospective Cohort Study - O'Connell, Nina; Oh, Jun; Arbeiter, Klaus; Büscher, Anja; Haffner, Dieter; Kaufeld, Jessica; Kurschat, Christine; Mache, Christoph; Müller, Dominik; Patzer, Ludwig; Weber, Lutz T.; Tönshoff, Burkhard; et al. (Frontiers in Medicine, 2022)
Background Infantile nephropathic cystinosis (INC) is a rare lysosomal storage disorder resulting in progressive chronic kidney disease (CKD) and a variety of extrarenal manifestations. This orphan disease remains a challenge for patients, their families and health care providers. There is currently no comprehensive study on patients’ clinical course in Germany and Austria. Methods A retrospective cohort study including 74 patients at eleven centers of care was conducted. Data on time of diagnosis, CKD stage, leukocyte cystine levels (LCL), extrarenal manifestations and treatment was collected from medical charts and subsequently analyzed using explorative statistics. Age at initiation of kidney replacement therapy (KRT) was evaluated by Kaplan-Meier analyses for different groups of patients. Results Patients were diagnosed at a median age of 15 months (IQR: 10-29, range: 0-110), more recent year of birth was not associated with earlier diagnosis. Oral cystine-depleting therapy (i.e. cysteamine) was prescribed at a median dose of 1.26 g/m2 per day (IQR: 1.03-1.48, range: 0.22-1.99). 69.2% of all 198 LCL measurements of 67 patients were within the desired target range ( ≤ 1 nmol cystine/mg protein). Median time-averaged LCLs per patient (n=65) amounted to 0.57 nmol cystine/mg protein (IQR: 0.33-0.98, range: 0.07-3.13) when considering only values at least one year after initiation of therapy. The overall median height of 242 measurements of 68 patients was at the 7th percentile (IQR: 1-25, range: 1-99). 40.5% of the values were the 3rd percentile. Patient sex and year of birth were not associated with age at initiation of KRT, but patients diagnosed before the age of 18 months required KRT significantly later than those patients diagnosed at the age of ≥ 18 months (p = 0.033): median renal survival was 21 years (95% CI: 16, -) versus 13 years (95% CI, 10, -), respectively. Conclusion Early diagnosis and initiation of cystine depleting therapy is important for renal survival in children with INC. Cysteamine doses and LCL showed that treatment in this cohort met international standards although there is great interindividual variety. Patient growth and other aspects of the disease should be managed more effectively in the future.